The impact of social grants on agricultural entrepreneurship among rural households in KwaZulu-Natal, South Africa - Sinyolo, Sikhulumile; Sinyolo, Sithembile A. (International Food Policy Research Institute, 2018)
This chapter investigates the conceptual and empirical linkages between social grants and agricultural entrepreneurship among rural households in the KwaZulu-Natal province of South Africa. Understanding the theoretical and empirical relationship between social transfers and smallholder entrepreneurship can enable policy makers to improve the design of rural development policy interventions and create synergies between cash transfers and poverty reduction by promoting enhanced agricultural productivity and production.